Glyphosate, AMPA, and metsulfuron-methyl retention in the main horizons of a typic argiudoll - Gonzalo Mayoral, Eliana Soledad; Aparicio, Virginia Carolina; De Geronimo, Eduardo; Fernandes, Gracieli; Dos Santos, Danilo Rheinheimer; Costa, José Luis (Taylor and Francis, 2022)
Retention is one of the processes controlling the behavior and fate of pesticides in soil. The objective of this work was to evaluate the adsorption and desorption of glyphosate, AMPA, and metsulfuron-methyl in the main horizons of a Typic Argiudoll destined for agricultural use. For this purpose, the batch equilibrium method was used at a range of concentrations for each compound. Desorption was performed in three consecutive steps after the adsorption experiment. The results obtained showed strong adsorption of glyphosate and AMPA in the three horizons, following the trend B > A > C, with weak desorption. Metsulfuron-methyl, on the other hand, showed weak adsorption in the three horizons, following the trend A > B > C, with relevant desorption. Our results allow us to identify metsulfuron-methyl as the compound that poses the greatest environmental risk in terms of the potential contamination of other areas and groundwater. However, despite their strong adsorption and weak desorption, glyphosate and AMPA also represent potential contaminants of other environmental matrices.